2020
DOI: 10.3389/fneur.2020.01016
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Hubs and Connectivity in Type 2 Diabetes Mellitus Without Mild Cognitive Impairment

Abstract: Background: Type 2 diabetes mellitus (T2DM)-related cognitive decline is associated with neuroimaging changes. However, only a few studies have focused on early functional alteration in T2DM prior to mild cognitive impairment (MCI). This study aimed to investigate the early changes of global connectivity patterns in T2DM by using a resting-state functional magnetic resonance imaging (rs-fMRI) technique. Methods: Thirty-four T2DM subjects and 38 age-, sex-, and education-matched healthy controls (HCs) underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
6
14
0
Order By: Relevance
“…The MoCA assesses the cognitive ability of subjects from the perspective of overall cognitive function and is currently widely used in cognitive-related research. In our study, we found that T2DM patients has lower MoCA scores than HCs, which was consistent with our previous studies ( 35 ). In addition, we found that the AVLT (immediate) scores were lower in the T2DM patients, suggesting that T2DM patients had immediate memory impaired.…”
Section: Discussionsupporting
confidence: 93%
“…The MoCA assesses the cognitive ability of subjects from the perspective of overall cognitive function and is currently widely used in cognitive-related research. In our study, we found that T2DM patients has lower MoCA scores than HCs, which was consistent with our previous studies ( 35 ). In addition, we found that the AVLT (immediate) scores were lower in the T2DM patients, suggesting that T2DM patients had immediate memory impaired.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies ( 15 , 18 ) have combined the DC and FC to explore the alteration of functional patterns in patients with neurological diseases. A recent study ( 13 ) reported increased DC of the right cerebellum and right fusiform gyrus among middle-aged patients with T2DM. Another study ( 18 ) with a similar population reported increased DC and FC value of the right anterior insula and dorsal anterior cingulate cortex.…”
Section: Introductionmentioning
confidence: 95%
“…Degree centrality (DC) is a method of measuring whole-brain connectivity based on the level of voxels, which effectively identifies the brain center. This method has been used in research related to diabetes ( 13 ), bipolar disorder ( 14 ), and Parkinson's disease ( 15 ). DC measures the connectivity of the whole brain to individual regions; this underlies the importance of the local region, termed the “brain hub” ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, resting‐state functional MRI (rs‐fMRI) has been used to investigate T2DM‐related changes in brain activity using amplitude of low‐frequency fluctuation (ALFF) of the blood oxygenation level‐dependent (BOLD) signal, and the changes in localized energy consumption using the regional homogeneity (ReHo) (Chen et al, 2014; Cui et al, 2014; Cui et al, 2015; Moheet, Mangia, & Seaquist, 2015; Xia et al, 2013). Other rs‐fMRI studies indicated that functional interactions of certain functional systems, measured by functional connectivity (FC) based on the temporal synchronizations of BOLD signals among distinct brain regions, could also be affected (Li et al, 2020). However, these studies mainly focused on the default mode network (DMN), a large‐scale resting‐state functional network mediating cognitive and emotional processes (Cui et al, 2014), and did not involve other functional systems, such as the attention (Xia et al, 2015), frontoparietal, and sensorimotor networks (SMNs) (Chen et al, 2015), in which the alterations were reported in the studies afterward.…”
Section: Introductionmentioning
confidence: 99%